Bank Competition, Combination of Industry and Finance, and Enterprise Innovation: Evidence from China - Xiaofang Tan; Yunshan Dong; Tongyu Fang (Complexity)
Bank competition promotes enterprises to obtain credit funds through market mechanisms, and a combination of industry and finance (CIF) has an important influence on establishing bank-enterprise relationship. Based on data of 2,245 manufacturing enterprises and branches of commercial banks in China from 2007 to 2019, this research establishes a moderated mediation model to verify whether CIF has a moderating effect on bank competition on enterprise innovation. The results are as follows. First, bank competition can both directly and indirectly promote enterprise innovation by alleviating financing constraints. Second, CIF has no moderating effect on the direct effect of bank competition on enterprise innovation but has a negative moderating effect on the first half of mediating effect.